F Formulation and Evaluation of Nano ECO-PINAS (Eco-friendly Pineapple Shampoo) Pineapple peel extract (Ananas comosus (L.) Merr) as an anti-dandruff agent - iwan Saka Nugraha; Wahyudi W Udi (Jurnal Ilmiah Farmako Bahari, 2026)
Nano ECO-PINAS (Eco-friendly Pineapple Shampoo) is a Nano shampoo made frompineapple peel waste. Dandruff is a scalp problem. One cause of dandruff is the fungusMalassezia furfur. Malassezia furfur is a cause of dandruff. This study aims to evaluatethe nano-preparation of pineapple peel shampoo (Ananas comosus) using physical testsin accordance with SNI standards and to assess its ability to inhibit the growth ofMalassezia furfur. The study used the True Experimental method, in which pineapplepeel is extracted, made into nanoparticles, and then formulated into various shampoo preparations. Evaluation includes particle size analysis (PSA), physical testing, and antifungal activity testing. The study showed that pineapple peel nanoextracts can be formulated into anti-dandruff shampoos that meet SNI physical test standards. All formulations have good physical quality, with a pH of 5.0–9.0, a viscosity of 400–4000 cps, stable foam, and a moisture content below 95%. The cleaning power ranges from 32–66%, with higher values indicating greater shampoo effectiveness in removing dirt and oil. Antifungal activity tests against Malassezia furfur showed that F3 had the largest inhibition zone (22.6 mm), followed by F2 (19.75 mm) and F1 (19.5 mm). For comparison, the blank inhibition zone was 1.86 mm, the ketoconazole positive control was 22.9 mm, and the comparative sample was 19.6 mm. The results of the One-Way ANOVA test (α = 0.05) showed a p-value of p = 0.00, indicating a significant difference between the pineapple peel nanoextract shampoos at concentrations of 3%, 6%, and 9% and the commercial shampoo. This data shows that the nanoextract of pineapple peel (Ananas comosus) formulated into the shampoo can inhibit the growth of Malassezia furfur.